2022
DOI: 10.1021/acsanm.1c04175
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Nanostructured Diamond Films on Glass Substrates by Low-Temperature Microwave Plasma-Enhanced Chemical Vapor Deposition for Applications in Nanotribology

Abstract: Low-temperature fabrication of superior nano-/microcrystalline diamond (NCD/MCD) films is a major thrust in diamond technology. The widely used seeding techniques applied on the substrate surface are usually harsh, lead to defect formation, and suffer from the lack of reproducibility in maintaining homogeneity and uniformity over nano-/microdimensions. Low-temperature growth of a significant diamond phase on purely untreated glass substrates is indeed a challenging task. Using CO2 as the supplementary gas-phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Moreover, the microwave plasma (MW) CVD is widely used to synthesize ND films on various chemically dissimilar surface substrates owing to the relatively low growth temperature, which utilizes the microwave energy to heat and decompose the gas molecules in the cavity into reactive groups, then finally obtain a high-quality ND film [ 65 , 66 , 67 , 68 , 69 , 70 ]. For example, Cheng C.Y.…”
Section: Fabrication Methods and Nucleation Process Of Nanodiamond Filmmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the microwave plasma (MW) CVD is widely used to synthesize ND films on various chemically dissimilar surface substrates owing to the relatively low growth temperature, which utilizes the microwave energy to heat and decompose the gas molecules in the cavity into reactive groups, then finally obtain a high-quality ND film [ 65 , 66 , 67 , 68 , 69 , 70 ]. For example, Cheng C.Y.…”
Section: Fabrication Methods and Nucleation Process Of Nanodiamond Filmmentioning
confidence: 99%
“…et al prepared the ND films and microdiamond films via a MW plasmas method in Figure 3 a. Additionally, it was suggested that the growth quality of ND film was restricted by the substrate surface pretreatment condition (scratching and seeding) rather than gas-phase condition [ 69 ]. Das D. et al successfully synthesized the ND films and even microdiamond films on glass substrates at the temperature of ∼300 °C using CO 2 /CH 4 /H 2 and provided a specific shadow-mask assembly to promote the nucleation of the diamond species and the diffusion growth of the nano-/micro diamond network on the untreated glass substrates, as shown in Figure 3 b [ 70 ]. The CO 2 was introduced as the supplementary gas to eliminate the amorphous carbon component in the synthesized nano-microdiamond.…”
Section: Fabrication Methods and Nucleation Process Of Nanodiamond Filmmentioning
confidence: 99%
See 2 more Smart Citations
“…This research has provided new ideas for wear-resistant coatings on steel alloys. At the same time, NCD film was successfully synthesized by Das et al [ 105 ] on an untreated glass substrate through spontaneous growth at low temperatures (~300 °C), providing a new method for the preparation of NCD films for nano-tribological application. During the deposition, CO 2 was used as a supplemental gas phase in the (CH 4 + H 2 ) plasma.…”
Section: Ncd For Tribological Applicationsmentioning
confidence: 99%